The effect of investor-level tax reform on payout policies : evidence from companies listed in selected sectors on the Johannesburg Stock Exchange - Nel, Rudie (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.